Status of wildlife at trophy hunting sites in the Ugalla Game Reserve of Western Tanzania. (September 2016) - Wilfred, Paulo; MacColl, Andrew D.C.
In western Tanzania's wildlife ecosystems, both commercial and subsistence uses of wildlife take place. Commercial use is largely through trophy hunting in designated hunting areas while subsistence use is predominantly carried out by local people for food and as a source of cash income. Assessing the status of wildlife populations in hunting areas is of supreme importance if unsustainable use is to be controlled. In this study, we carried out road transect surveys to estimate the density, group size and sex ratio of selected species of exploited wildlife in Ugalla Game Reserve, western Tanzania, to determine whether population characteristics differed between the Ugalla east and Ugalla west hunting sites. Overall, estimates of density and group size were higher at Ugalla east than Ugalla west. Of the individual species, the helmeted guineafowl had the highest population density, followed by impala and topi. Waterbuck had the lowest population density. When comparing our findings with population densities reported in other studies, especially in the more protected Katavi National Park in western Tanzania, our estimates were much lower. Sex ratios varied considerably among species although they were generally skewed towards females. Future studies should integrate data from subsistence and trophy hunting and evaluate the status of wildlife taking into account habitat characteristics.